Tansanal total mesorectal excision (TaTME): systematization and mediated results in 10 patients - Neiva,Guilherme Inácio Bertoldo de Melo e Patriarca da Silva (2020)
Abstract Background Transanal total mesorectal excision is a surgical technique for minimally invasive resection of the rectum and perirectal tissues. It is indicated for patients with medial and distal rectum cancer confined to the mesorectal envelope. This study describes a series of patients undergoing transanal total mesorectal excision. Methods Ten patients were selected to undergo transanal total mesorectal excision using the SILS-Port® platform. All patients included here had middle or low rectal cancer. Abdominal access for proximal colon mobilization was performed by laparoscopy in all cases. As a rule, in 9 of the 10 cases, the surgical specimen was removed transanally. Results During a 41-month period, 10 patients underwent transanal total mesorectal excision based on curative intent. The first indication for transanal total mesorectum excision was medial and distal rectal cancer, locally invasive and confined to the mesortal envelope. The median age of patients with rectal cancer at the time of surgery was 61 years (mean 59.4 years, range 22–78 years), with 80% (8) female and 20% (2) male. The median surgical time was 305′ (mean 314′, range 260‒420′). The median postoperative length of stay was five days (average of 7.3 days, interval of 3–23 days). There was no postoperative mortality. Surgical complications included postoperative ileus (n = 1), bladder paresis (n = 1), and ileostomy stenosis (n = 1). All patients had negative surgical margins for neoplasia and more than 12 resected lymph nodes. The tumors were between 1 and 9 cm from the anal margin. Conclusion Total transanal mesorectal excision has been shown to be a viable method for oncologic resection of locally advanced rectal cancer with curative intent.